2007
DOI: 10.1002/nur.20190
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of mother–premature infant interactions

Abstract: This study's purpose was to examine whether child characteristics, child illness severity, maternal characteristics, maternal psychological well-being, and paternal support influenced interactions between 108 premature infants and their mothers. Mothers with singletons or more infant illness stress showed more positive involvement. Mothers with less infant illness stress, less education, or less participation in caregiving by fathers showed more negative control. First-time mothers and mothers of singletons pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 59 publications
8
126
1
1
Order By: Relevance
“…Although the literature indicates associations between maternal characteristics, as well as neonatal, and the performance of the maternal role (3,6,11) , it was not detected in this sample. However, it was found that women who were present at the hospital less frequently presented with a higher number of DC of the ND studied.…”
Section: "Demonstrates Disruption In Caretaking Routines"contrasting
confidence: 39%
See 2 more Smart Citations
“…Although the literature indicates associations between maternal characteristics, as well as neonatal, and the performance of the maternal role (3,6,11) , it was not detected in this sample. However, it was found that women who were present at the hospital less frequently presented with a higher number of DC of the ND studied.…”
Section: "Demonstrates Disruption In Caretaking Routines"contrasting
confidence: 39%
“…This feeling was related to the risk of death of the child, the possible sequelae, the physical aspect of the NB and his fragility, the fear of manipulating the child and not properly taking care of him or hurting him, as well as the equipment and environment of the neonatal unit (1,6,(11)(12)15) . A mother that experienced this DC may have behaviors that could be incorrectly interpreted by the team, if not investigated and evaluated with interest and depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, a representação que a mãe vai construindo acerca do seu bebé ao longo da gravidez e que tende a facilitar o envolvimento afetivo e a interação no pós parto (Stern, 2002), dissipa-se nos partos pré-termo. Deste modo, para além dos "processos fantasmáticos" que os pais experienciam, como o receio pela sobrevivência e desenvolvimento do bebé, a imaturidade do recém-nascido poderá dificultar a sua estimulação e consequentemente, o estabelecimento de interações dos progenitores com o bebé (Holditch- Davis, Schwartz, Black, & Scher, 2007).…”
Section: Prematuridade Em Mães Primíparas E Multíparas: Implicações Punclassified
“…Fathers are also considered as a key element in supporting the mother and infant (12,13). This issue has been emphasized in many studies (2,10,14), indicating that mothers who are deprived of the support of the infant's father have less positive interaction with the infant than those receiving such support (15). Studies suggest the positive impact of creating opportunities for parent empowerment (COPE) programs on parents' mental health; however, more studies are recommended on all aspects of Copyright © 2017, Iranian Journal of Pediatrics.…”
Section: Introductionmentioning
confidence: 99%